Abundance and morphometry of the freshwater bivalve Prisodon obliquus at Maratauíra river, Abaetetuba, State of Pará, northern Brazil - Barros, Mara Rúbia Ferreira; Chagas, Renata R D; dos Santos, Wagner Cesar Rosa; Abreu, Valdo Sena; da Silva, Rosana Esther Oliveira; Freire, Cibele Cristina Oeiras; dos Santos-Neto, Guilherme da Cruz; Herrmann, Marko (PANGAEA, 2019)
Abundance and morphometry of freshwater mussels collected in the Maratauíra river, Abaetetuba, Pará between September 2016 and September 2017. Measuring the anteroposterior length of each individual. In all, 8,399 individuals were collected, ranging in length from 7.71 to 104.63 mm.
Keywords: Benthos; freshwater mussel; mollusk